Interactive Learning Tool for System of Linear Equations: Bridging the Gap Between Novice and Expert Through MATLAB-Based Solutions - Reem A. Alnanih; Lamiaa A. Elrefaei (IEEE Access)
Interactive learning tools are increasingly used to visually convey complex concepts, enhancing students’ understanding and engagement during the learning process. This paper presents an adaptation of interactive learning technology aimed at simplifying the learning of complex concepts through the design and development of a MATLAB-based desktop application. This interactive learning tool enables users to solve systems of linear equations independently, covering both the direct method (Gaussian elimination) and iterative methods (Gauss-Seidel 1, Gauss-Seidel 2, and an improved Gauss-Seidel). Users can interactively apply these techniques to sample systems and receive immediate feedback, facilitating self-paced learning. The tool allows learners to compare methods based on criteria such as computation time, iteration count, and error margin, using MATLAB solutions as a benchmark for accuracy on systems of any size. Usability testing evaluated objective factors, including task effectiveness (measured by completion rate) and efficiency (assessed by time taken to complete tasks). Additionally, a user satisfaction questionnaire assessed subjective factors across four categories: look and feel, interaction, feedback, and functionality. The System Usability Scale (SUS) provided an overall measure of user satisfaction with the tool. A total of 20 participants—10 experts with prior knowledge of linear equations and 10 novices without such knowledge—were involved in the evaluation. Results indicated that the tool enabled both groups to successfully complete eight assigned tasks with no significant difference in task completion time. Furthermore, statistical analysis of the post-test questionnaire revealed high levels of satisfaction on the SUS for both groups, with no significant differences in user satisfaction between novices and experts.